Drawings of observation in the architecture workshop. Between subjective expression and objective representation - Cañete Islas, Omar (Facultad de Arquitectura, Urbanismo y Diseño, 2018)
We intend to systematize a series of teaching experiences, related to develop a compressive field in architectural drawing, usually known as sketch. In a more theoretical-pedagogical sense, it is sought that the students could explore and transit in a sensitive, but graduated and continuous way between two planes: a) Individual expression, and b) a formal composition. Although their differences (objective v/s subjective point of view) both aspects are part from a same generative, dynamic and complex order